Incidence of 1-lyponatraemia in Patients with lschemic Stroke: Our Experience at RMCH - Mahmood, I; Rahman, MK; Khan, MMR; Haque, MA; Chowdhury, MMH; lqbal, A; Rashid, MH; Ahad, MA; Kamal, SM (TAJ: Journal of Teachers Association, 2009)
Hyponatraemia is a common electrolyte disorder in central nervous system (CNS) disease and is often attributed to the syndrome of inappropriate secretion of antidiuretic hormone (SIADH). By contrast, there are patients with intracranial disease who develop hyponatraemia with similar characteristics, but differ in that there is clinical evidence of a contracted extracellular fluid (ECF) volume. This form of hyponatraemia is caused by excessive renal Na excretion, resulting from a centrally mediated process, and is termed cerebral salt wasting (CSW). Hyponatraemia, if acute that is developed within hours or days may cause confusion, coma restlessness or seizures. 72 patients with ischemic stroke admitted at RMCH were selected for this prospective cohort study. Among the subjects 34 (47.22%) cases were found to have hyponatraemia. The number was quite large and screening patients with stroke for electrolytes may be extremely helpful to reduce mortality and morbidity. TAJ 2009; 22(1): 212-215